2008
DOI: 10.1177/104063870802000215
|View full text |Cite
|
Sign up to set email alerts
|

Identification of complex vertebral malformation carriers in Chinese Holstein

Abstract: Abstract. Complex vertebral malformation (CVM) is a monogenic autosomal recessive hereditary defect of Holstein dairy cattle. It is caused by a point mutation from G to T at the nucleotide position 559 in bovine solute carrier family 35, member 3 gene (SLC35A3), which changes the amino acid sequence of uridine 59-diphosphate-N-acetylglucosamine transporter protein from a valine to a phenylalanine in position 180. The elite U.S. Holstein sire Penstate Ivanhoe Star was identified as the common ancestor of the cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 5 publications
0
24
0
Order By: Relevance
“…Although the frequency of CVM carriers found in this study was very low, higher frequencies of CVM carriers were reported by Meydan et al (2010) in Turkish Holstein cows (3.4%), Ghanem et al (2008) in Japanese Holstein cows (13%), and Chu et al (2008) in Chinese Holstein bulls (15%). The frequency of carriers for CVM in some countries has been reported at alarming levels, e.g., Swedish Holsteins (23%) (Berglund et al, 2004) and Polish Holstein-Friesian bulls (24.79%) (Ruść and Kamiński, 2007).…”
Section: Discussionmentioning
confidence: 81%
“…Although the frequency of CVM carriers found in this study was very low, higher frequencies of CVM carriers were reported by Meydan et al (2010) in Turkish Holstein cows (3.4%), Ghanem et al (2008) in Japanese Holstein cows (13%), and Chu et al (2008) in Chinese Holstein bulls (15%). The frequency of carriers for CVM in some countries has been reported at alarming levels, e.g., Swedish Holsteins (23%) (Berglund et al, 2004) and Polish Holstein-Friesian bulls (24.79%) (Ruść and Kamiński, 2007).…”
Section: Discussionmentioning
confidence: 81%
“…Chu et al (2008) reported that the percentage of CVM carriers in China was 43.6%, much higher than our finding, because the Holstein cattle sample in their study comprised 68 frozen semen samples from at-risk Chinese Holstein bulls and 602 cows whose sires included 10 confirmed at-risk bulls; these bulls were selected according to the list of CVM carrier sires published by the United States and Canada, as well as the Chinese Holstein sire pedigrees, and probably were potential CVM carriers. In our study, 217 cows and 125 bulls were randomly collected from a Holstein cattle population in south China, whose pedigree and CVM carrier status were not clear, and this may be the reason that the percentage of CVM carriers in our study is different from that reported by Chu et al (2008). Anyhow, the CVM gene exists in China, and it is essential to detect CVM and report the distribution of CVM carriers in the population of Holstein cattle in south China.…”
Section: Several Methods Used To Detect Cvm Have Been Reportedmentioning
confidence: 99%
“…The use of CVM carriers will inevitably result in economic losses in the management of dairy cattle herds Thus, many countries have carry out the detection of CVM and report the distribution of CVM carriers (Berglund et al, 2004;Thomsen et al, 2006;Rusc and Kaminski, 2007;Ghanem et al, 2008;Chu et al, 2008). The frozen semen and embryos of our country are imported from the United States and Denmark and other countries.…”
Section: Several Methods Used To Detect Cvm Have Been Reportedmentioning
confidence: 99%
See 2 more Smart Citations